(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2024)
Existential philosophy and related phenomenological practices have contributed to ways of being that we now label as postmodern. The idea that this is new, or that there are ’pre’ or ’post’ eras is questionable. The anxieties that we experience, due to the lack of an essential self, have always been present. Attending to our situated embodied existence can help.